Imigrantes e soldados - D'Araujo, Maria Celina (Revista Brasileira de Estudos de Defesa, 2023)
Resenha de: Grazia Scoppio e Sara Grego (Edit.) McGill-Queen’s University Press, 2022. The Power of Diversity in the Armed Forces: International Perspectives on Immigrants’ Participation in the Military